IMPLEMENTASI PROGRAM PENANGGULANGAN HIV/AIDS DI LEMBAGA PEMASYARAKATAN CILACAP DAN NUSAKAMBANGAN - Sujatmiko Sujatmiko; Ali Rokhman; Simin Simin (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2016)
Outbreak of HIV / AIDS has reached an alarming stage that the UN put in one of the Millennium Development Goals (MDGs) are also targeted to prisons, in which, there are prisoners / detainees, including key sections of the population or high-risk groups. Seeing these conditions is necessary strategic steps to prevent and deal with the issue of HIV / AIDS in prison. One of the efforts is the presence of HIV / AIDS in prison. This type of research used in this research is descriptive qualitative approach. Research study on the implementation of program on HIV / AIDS in prisons / detention centers and model analysis of the data used in this study is a model of analysis of empirical data. Results are ekpected to improve of to benefit and rate changes for the better in implementing HIV / AIDS that is reaching goals such as Getting to Zero zero new infection, zero discrimination, and zero related death. With limited resources both human resources and other resources of HIV / AIDS have been able to walk although there are some activities that are constrained. Limitations of resources, especially funding critical factor in the program include the lack of funding from the government requires the collaboration with other actors and implement a model of multi-level governance is a model of interdependence of different territorial government or by non-governmental actors that if it had not anticipated the will ultimately negatively impact dependency. Keywords: policy implementation , HIV/AIDS, prisons